Fenomenology Study : The role of Occupational Health Nurses (OHN) in Emergency and Disaster Services - Albyn, Devanda Faiqh; Harianto, Dwi Cahyo; Widodo, Agus Wahyu; Nurdiansyah, Yuli; Hasdar; Hak, Denny Achsanul; Wibowo, Tri Suryo; Pradana; Ardiansyah, Fredi; Bakhtiyar, Rizkhy; Rifanto, Eko Adi (Babali Emergency and Disaster Research, 2023)
Background: Education and experience are important components in the ability of occupational health nurses (OHN) to improve high-quality care and competency. OHNs will increasingly need the skills and knowledge to base care on the best evidence, to use critical thinking and demonstrate advanced leadership and decision-making skills to develop and improve services in more complex and diverse occupational health care environments. The purpose of this study was to identify the professional development needs of OHNs in occupational health settings. Method: Explorative, descriptive, generic contextual and qualitative research methods were used in this research. A purposive sampling method was used when OHNs were surveyed to describe their personal needs for professional development in occupational health settings. Data was collected through semi-structured individual interviews. Eight interviews were conducted by interviewers who had a doctorate in public health nursing and a qualification in occupational health and were affiliated with a private occupational health agency at the time of the study. The interview was conducted at the time August 2012. Results:  The results of this research reveal four major themes, namely obstacles that hinder OHNs from developing positive aspects professionally identified by OHNs regarding professional development needs, OHN professional development needs and suggestions on how to meet OHN's professional development needs. Conclusion:There is a need for OHNs to identify their professional development needs and recommendations to be made to meet these needs